Ice distribution in Hornsund fjord, Svalbard from Envisat ASAR (2002-2012) - Vincent Papin; Zuzanna M Swirad; A Malin Johansson; Eirik Malnes (PANGAEA, 2025)
This dataset contains binary maps of ice (1) and open water (0) in Hornsund fjord, Svalbard at 50 m resolution. The maps are based on the Envisat ASAR archive between 30.10.2002 and 7.04.2012 with an average image frequency of 3.25 days. This dataset is an extension of the Sentinel-1A/B-based one (doi:10.1594/PANGAEA.963167, Swirad et al., 2023) processed in the way described in Swirad et al., 2024, and RADARSAT-2-based one (doi:10.1594/PANGAEA.969031; Swirad et al., 2024). A document containing details on the scenes and polarisation channels used, the number of segments and the level of manual editing is provided.